Utilization of Big Data In E-Commerce Business - Nico Fernando; Mery Mery; Jessica Jessica; Johanes Fernandes Andry (IAIC International Conference Series, 2020)
In this day and age with the internet brings revolution to the way all fields work, especially in the field of business. With the internet technology data became big and known as "Big Data". The development of big data has increased significantly so that it can be utilized in various fields, especially in business areas that have been implemented with internet technology. This electronic buying and selling media have a wide range such as from small to large stores that can utilize media or with a site. This makes users always need this technology, so an E-commerce can also be said to be the largest data-producing media. This study addresses the problem of the extent to which big data generated from E-commerce can affect business and provide benefits for business organizations such as expanding the scope of transactions, supporting decision-making, and others. The research method used in compiling this research is to collect data and information and then conduct processing and analysis of the data. So it is expected from the results of utilization of big data in this E-commerce business that has been processed can provide support especially in making decisions with cluster results that have been obtained for example such as to know the most sales patterns in order to be able to add stock to certain goods and determine promotions based on future sales. The study concluded that based on gift shop sales data, the average item purchased by the store's customers is found in items that are included in cluster group 0 so that the gift shop can increase the stock of items contained in cluster group 0.